2021
DOI: 10.3390/mi12101256
|View full text |Cite
|
Sign up to set email alerts
|

New Ultrasensitive Sandwich-Type Immunoassay of Dendritic Tri-Fan Blade-like PdAuCu Nanoparticles/Amine-Functionalized Graphene Oxide for Label-Free Detection of Carcinoembryonic Antigen

Abstract: The early detection of tumor markers has an effective role in the treatment of cancer. Here, a new sandwich-type electrochemical immunosensor for early label-free detection of the cancer biomarker carcinoembryonic antigen (CEA) was developed. Dendritic tri-fan blade-like PdAuCu nanoparticles (PdAuCu NPs)/amine functionalized graphene oxide (NH2-GO) were the label of secondary antibodies (Ab2), and Au nanoparticle-decorated polydopamines (Au/PDA) were immobilized on a screen-printed carbon electrode (SPCE) as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…and 6.7 fg/mL as detection limit. Similarly, Xu et al [108] also reported another sandwich type EC immunosensor for CEA quantification (Figure 13). The screenprinted carbon electrode (SPCE) used as the working electrode was modified with AuNPsdecorated polydopamines (Au/PDA), which served as substrate material onto which primary antibody (Ab1) was immobilized.…”
Section: Sandwich-type Ec Immunosensors For Cea Detectionmentioning
confidence: 75%
“…and 6.7 fg/mL as detection limit. Similarly, Xu et al [108] also reported another sandwich type EC immunosensor for CEA quantification (Figure 13). The screenprinted carbon electrode (SPCE) used as the working electrode was modified with AuNPsdecorated polydopamines (Au/PDA), which served as substrate material onto which primary antibody (Ab1) was immobilized.…”
Section: Sandwich-type Ec Immunosensors For Cea Detectionmentioning
confidence: 75%
“…Electrochemical immunosensors have been a tool in the early monitoring and diagnosis of cancer. Our group demonstrated the use of this method as a label-free detection route of the cancer biomarker by dendritic tri-fan blade-like PdAuCu nanoparticles/aminefunctionalized graphene oxide [ 30 ]. In order to obtain a high sensitivity in the electrochemical immunosensors, trimetallic nanomaterials have broad applications due to their excellent properties, e.g., superior catalytic activity, better durability, and larger surface-active areas.…”
Section: Resultsmentioning
confidence: 99%
“…Screen printing technology was used to make on-site and point-of-care biosensors for their easy miniaturization, lower cost, disposable nature, and mass production [ 29 ]. A screen-printed carbon electrode (SPCE) is often used, with the fabrication of electrochemical immunosensors, to monitor physiological indicators in the process of diagnosis [ 30 ]. In this work, an SPCE was employed to design an electrochemical immunosensor for the efficient detection of colorectal cancer-derived exosomes ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 Xu et al found a new ultrasensitive sandwich-type immunoassay biosensor to detect the CEA concentration with a detection limit of 0.07 pg mL −1 and a linear detection range from 0.1 pg mL −1 to 200 ng mL −1 . 17 However, these methods need complex sample preparation processes or bulky detection equipment, which restricts their application in resource-limited settings and point-of-care testing (POCT) away from central laboratories. In biosensing detection, microfluidic devices have recently received increasing attention.…”
Section: Introductionmentioning
confidence: 99%